2013
DOI: 10.1186/1471-2458-13-663
|View full text |Cite
|
Sign up to set email alerts
|

Serum calcium and risk of gastrointestinal cancer in the Swedish AMORIS study

Abstract: BackgroundObservational studies have indicated that high calcium intake may prevent colorectal cancer, but as for randomized trials the results are inconclusive. Meanwhile, limited data on the link between serum calcium and cancer risk is available. We investigated the relation between serum calcium and risk of different gastrointestinal cancers in a prospective study.MethodsA cohort based on 492,044 subjects with baseline information on calcium (mmol/L) and albumin (g/L) was selected from the Swedish Apolipop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 30 publications
2
30
0
Order By: Relevance
“…The Swedish AMORIS cohort study, which analyzed serum calcium and the association with gastrointestinal cancers, found no strong association between albumin adjusted-serum Ca and incident gastric cancer, although there was a suggestive inverse association in the highest vs. lowest quartiles of serum Ca. 27 Among other limitations of our study, serum calcium intake is not reflective of dietary intake or total body stores and is influenced by many other factors including albumin level; dietary intake, on the other hand, is the major determinant of total body calcium balance. 27,28 Gastric cancer-related mortality was not reported among Chinese men, nor was the risk of incident gastric cancer evaluated.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The Swedish AMORIS cohort study, which analyzed serum calcium and the association with gastrointestinal cancers, found no strong association between albumin adjusted-serum Ca and incident gastric cancer, although there was a suggestive inverse association in the highest vs. lowest quartiles of serum Ca. 27 Among other limitations of our study, serum calcium intake is not reflective of dietary intake or total body stores and is influenced by many other factors including albumin level; dietary intake, on the other hand, is the major determinant of total body calcium balance. 27,28 Gastric cancer-related mortality was not reported among Chinese men, nor was the risk of incident gastric cancer evaluated.…”
Section: Discussionmentioning
confidence: 81%
“…27 Among other limitations of our study, serum calcium intake is not reflective of dietary intake or total body stores and is influenced by many other factors including albumin level; dietary intake, on the other hand, is the major determinant of total body calcium balance. 27,28 Gastric cancer-related mortality was not reported among Chinese men, nor was the risk of incident gastric cancer evaluated. Results for NCGA and CGA were also not presented, which is relevant given their epidemiologic and biologic differences, as well as differences in clinical management and prognosis.…”
Section: Discussionmentioning
confidence: 81%
“…2) Another study demonstrated a highly significant negative association of cancer and serum calcium levels in women [17]. 3) A positive link between serum calcium, esophageal cancer, and colorectal cancer in women was found in a prospective study [18]. 4) For prostate cancer, there were two large Swedish studies.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore accounted for period of diagnosis in our analyses as a proxy for difference in screening and treatment over time. Information on race/ethnicity was not available; however, the AMORIS cohort was similar to the general working population of Stockholm (Wulaningsih et al, 2013b) that comprised B80% Swedish-born individuals in 2000 (Statistics Sweden, 2015). Serum LDH increases because of other conditions such as myocardial infarction, inflammation and tissue injury (Drent et al, 1996;Kemp et al, 2004;Kato et al, 2006), and therefore is not a specific marker of tumour.…”
Section: Discussionmentioning
confidence: 99%